A Study on Ricci Solitons in Kenmotsu Manifolds. (7th March 2013) - Bagewadi, C. S.; Ingalahalli, Gurupadavva; Ashoka, S. R.
Abstract : We study and obtain results on Ricci solitons in Kenmotsu manifolds satisfying R ( ξ, X ) · B = 0, B ( ξ, X ) · S = 0, S ( ξ, X ) · R = 0, R ( ξ, X ) · P ¯ = 0, and P ¯ ( ξ, X ) · S = 0, where B and P ¯ are C-Bochner and pseudo-projective curvature tensor.